Salto desde la estratósfera - Oré, Casio R. (2013)
On sunday october 14, 2012, the Austrian Felix Baumgartner did a spectacular jump in Roswell, New Mexico. He ascended 39 km high in a helium contained globe and jumped. In this work I try to applay physical laws to understand the details of the trajectory.